Desenvolvimento profissional docente de professoras de CEI em tempos de crise: a importância da arte e dos diários de bordo - Penteado, Paula de Camargo (2023)
The time experienced by many teachers in 2020, due to the social isolation caused by the Covid-19 pandemic, was atypical and transformed the space-time relations within educational institutions. Along with many challenges, such as remote teaching, teachers from Early Childhood Education Centers (CEI) in the city of São Paulo did not have guaranteed weekly study and training hours mandated by law until then. This made 2020 a unique time for research, study, and professional development for these teachers. Based on this, this research investigates the meanings attributed to the formative moments experienced by teachers from a partnering CEI in São Paulo during social isolation. To achieve this, it revisits the pandemic context documented in diaries. The study also aims to identify the feelings caused by teachers' separation from the school, examining how professionals report and identify the impact of formative moments during the pandemic on their work today. Lastly, it aims to gather clues, based on experience, for the professional development of teachers in partnering CEIs. The qualitative research draws inspiration from narrative research, guided by authors such as Passeggi (2021), Prado and Serodio (2018), Souza and Meirelles (2018), and others. The research involves a documentary analysis, referred to here as an inventory, of the diaries written by three teachers from the institution in question. Additionally, a reflective group, referred to as an inventorial inventory, allowed for a meta-reflection on the experiences of 2020. The study embraced a methodology that, at various points, aligns with art, bringing sensitivity and subjectivity to the forefront of the investigation. It recognizes that humans are holistic beings and their emotions must be considered, especially in educational research. The data produced was analyzed using prosa analysis, as outlined by André (1986), and cartography, as outlined by Kastrup (2020). Preliminary results indicate the importance of diaries for professional development in teaching, as endorsed by Zabalza (2004), while also highlighting art as a tool for such development, suggesting 7 clues for qualified professional development: principle of reflection on practice, principle of authorship, principle of participation, principle of collectivity, principle of considering the meanings attributed to a given event, principle of working conditions and principle of homology of processes